GE_GERICHTE C/111/2012 vom 21. November 2014 - GE Cour de justice (2014)
PRÊT DE CONSOMMATION; RÉSILIATION ANTICIPÉE; INTERPRÉTATION(SENS GÉNÉRAL); FARDEAU DE LA PREUVE; INDEMNITÉ(EN GÉNÉRAL) | CO.1.1; CO.5.1; CO.7.1; CO.18; CO.163.3; CC.8; CPC.317.1